Revisiting a diagnosis of cystic fibrosis – Uncertainties and considerations. (June 2022) - Balfour-Lynn, I.M.; Puckey, M.; Simmonds, N.J.; Davies, J.C.
Abstract: There is now increased knowledge and experience of newborn screening around the world. There is also a better understanding of CF gene analysis, informed by international databases. This has resulted in a small number of children and adults having their diagnosis of CF reversed. This article illustrates this issue with three cases. It considers how best to tell children and adults with their families, and the reactions that may be encountered. It also discusses practical issues of removing the diagnosis.